INNOVATIVE METHODS IN THE PROCESS OF HIGHER MATHEMATICS FOR FUTURE MILITARY ENGINEERS - Khomuyk, Irina; Ivanchenko, Ievgeniia; Maslii, Oleg; Gorlichenko, Marina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
In today's conditions, special attention is paid to ensuring the defense capability of the state, which requires from the system of higher military education the training of a future officer capable of solving military-technical problems of any complexity based on the basic knowledge that he received while studying at a higher military educational institution. As the most regulated sphere of education, military education requires the introduction of innovative technologies that will increase the interest of cadets and the degree of materials assimilation, in particular, in the academic discipline «Higher Mathematics». The problem of choosing teaching technologies in higher military educational institutions can be recognized as one of the most important, requiring theoretical and practical development at the level of teaching of each individual discipline and educational process in general. The purpose of the article is theoretical and empirical substantiation of the modern innovative technologies use in the process of studying higher mathematics in higher military educational institutions. The following methods were used during the research: theoretical ‒ the study and analysis of literature on the introduction of innovative technologies into the educational process of higher educational institutions and higher military educational institutions; modeling; empirical ‒ observation, conversation, testing, methods of statistical analysis for the transformation of empirical data into quantitative indicators. The purpose of our experimental study was to determine the impact of the innovative technologies use on the learning process in higher military educational institutions. The results of the experiment showed the effectiveness of the proposed innovative technologies in the process of fundamental training of future military engineers.